Development of a novel AAK1 inhibitor via Kinobeads-based screening - Akari Yoshida; Satomi Ohtsuka; Fumiya Matsumoto; Tomoyuki Miyagawa; Rei Okino; Yumeya Ikeda; Natsume Tada; Akira Gotoh; Masaki Magari; Naoya Hatano; Ryo Morishita; Ayano Satoh; et al. (Scientific Reports, 2024)
Abstract A chemical proteomics approach using Ca2+/calmodulin-dependent protein kinase kinase (CaMKK) inhibitor–immobilized sepharose (TIM-063-Kinobeads) identified main targets such as CaMKKα/1 and β/2, and potential off-target kinases, including AP2-associated protein kinase 1 (AAK1), as TIM-063 interactants. Because TIM-063 interacted with the AAK1 catalytic domain and inhibited its enzymatic activity moderately (IC50 = 8.51 µM), we attempted to identify potential AAK1 inhibitors from TIM-063-derivatives and found a novel AAK1 inhibitor, TIM-098a (11-amino-2-hydroxy-7H-benzo[de]benzo[4,5]imidazo[2,1-a]isoquinolin-7-one) which is more potent (IC50 = 0.24 µM) than TIM-063 without any inhibitory activity against CaMKK isoforms and a relative AAK1-selectivity among the Numb-associated kinases family. TIM-098a could inhibit AAK1 activity in transfected cultured cells (IC50 = 0.87 µM), indicating cell-membrane permeability of the compound. Overexpression of AAK1 in HeLa cells significantly reduced the number of early endosomes, which was blocked by treatment with 10 µM TIM-098a. These results indicate TIM-063-Kinobeads-based chemical proteomics is efficient for identifying off-target kinases and re-evaluating the kinase inhibitor (TIM-063), leading to the successful development of a novel inhibitory compound (TIM-098a) for AAK1, which could be a molecular probe for AAK1. TIM-098a may be a promising lead compound for a more potent, selective and therapeutically useful AAK1 inhibitor.